Preparation method of sodium ferromanganese phosphate-pyrophosphate positive electrode material

By adjusting the iron-manganese ratio in the manganese-ferromanganese solution and performing in-situ carbon-encapsulation and vapor-phase deposition coating, a high-capacity and high energy density sodium manganese-ferromanganese pyrophosphate positive electrode material is prepared, which solves the problems of poor conductivity of existing materials and easy fall off of carbon layers, which is suitable for the practical application of sodium ion batteries.

CN119569014AInactive Publication Date: 2025-03-07TIANJIN WASTSODIUM TECHNOLOGY RESEARCH & DEVELOPMENT CO LTD +1

Patent Information

Application Number
CN202510131043.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In practical applications, sodium ferric pyrophosphate positive electrode material has low open circuit voltage, low electronic conductivity, and easy decarbonization during the airflow crushing process, resulting in poor conductivity.

Method used

A method of preparing a positive electrode material of sodium manganese pyrophosphate is adopted. By adjusting the molar ratio of iron ions to manganese ions in the ferromanganese solution, and heating reactions are carried out under a nitrogen environment, followed by primary in-situ carbon coating and secondary vapor deposition coating to form a stable carbon coating layer.

Benefits of technology

It improves the charge and discharge capacity, rate performance and conductivity of the positive electrode material of ferromanganese pyrophosphate, solves the problem of easy falling off of the carbon layer during the processing of the material, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569014A_ABST
    Figure CN119569014A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium ion batteries, and particularly relates to a preparation method of a sodium ferromanganese phosphate-pyrophosphate positive electrode material. The ferromanganese phosphate pyrophosphate positive electrode material is prepared through a solid phase method, the process is simple, the cost is low, and the method is suitable for industrial production; according to primary in-situ carbon coating and secondary organic solvent vapor deposition coating provided by the invention, stable carbon coating is formed on the surface of the positive electrode material, and the carbon coating is uniform, so that the problem that a carbon layer is easy to fall off in the processing process of the material is solved to a certain extent; the sodium manganese ferric phosphate pyrophosphate positive electrode material prepared by the method provided by the invention is stable in structure, and has relatively high charge-discharge capacity and excellent rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a method for preparing a sodium ferromanganese phosphate pyrophosphate positive electrode material. Background Art

[0002] The cathode materials of sodium-ion batteries currently in the commercialization stage mainly include layered oxides, sodium ferrous sulfate, sodium ferric pyrophosphate and other cathode materials. Sodium ferric pyrophosphate has outstanding advantages such as a wide source of raw materials, good safety, long cycle life, green and pollution-free, and easy large-scale preparation. It has become a more ideal cathode material for energy storage sodium-ion batteries and has broad application prospects in the fields of fixed energy storage, start-stop, etc. However, in actual applications, sodium ferric pyrophosphate materials have the problem of low open circuit voltage of the material, resulting in low battery energy density; the low intrinsic electronic conductivity of the material is coupled with the phenomenon of decarbonization of the material during the airflow crushing process. Under these two factors, the conductivity of the material is very poor.

[0003] Compared with sodium ferric pyrophosphate (Na4Fe3(PO4)2P2O7), sodium ferric manganese pyrophosphate (Na4Mn 3-x Fe x (PO4)2P2O7) has a high potential of about 4.0V and almost the same theoretical capacity. Under the condition of equal capacity, the energy density of sodium manganese iron pyrophosphate battery will be nearly 30% higher than that of sodium iron pyrophosphate. However, both sodium manganese iron pyrophosphate material and sodium iron pyrophosphate material have the defect of low conductivity. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a high-capacity, high-energy-density sodium manganese iron phosphate positive electrode material.

[0005] The present invention provides a method for preparing a sodium ferromanganese phosphate pyrophosphate positive electrode material, wherein the chemical formula of the sodium ferromanganese phosphate pyrophosphate positive electrode material is: Na y Mn x Fe b [(PO4)2P2O7] t C1C2, wherein 4.05≤y≤4.1, 0.9≤x≤2.1, 0.9≤b≤2.1, 1.005≤t≤1.013; C1 is a primary in-situ carbon coating, and C2 is a secondary vapor deposition coating; the method comprises the following steps: (1) Mixing ferrous sulfate heptahydrate, manganese sulfate monohydrate and pure water to obtain a ferromanganese solution, wherein the molar ratio of iron ion concentration to manganese ion concentration in the ferromanganese solution is Mn:Fe=3-a:a, where a is 0.9≤a≤2.1; then adjusting the pH value to about 2 with sulfuric acid; heating the ferromanganese solution under a nitrogen environment, wherein the heating condition is 400rpm and 60°C; then adding a 1 mol / L oxalic acid solution at 60°C to react, and adjusting the pH value to 2 with 6 mol / L ammonia water; then reacting for 3 hours, filtering, washing with an ammonium oxalate solution, and drying to obtain ferromanganese oxalate; (2) crushing ferromanganese oxalate, performing a first grinding, adding a sodium source compound, a phosphorus source compound and a carbon source, mixing evenly, performing a second grinding and spray drying to obtain a precursor; (3) The precursor is crushed and placed in a pot, and an organic solution is introduced into the pot under the protection of an inert gas for sintering to obtain a sodium manganese iron phosphate positive electrode material.

[0006] Preferably, the ammonium oxalate solution is a 0.1 mol / L ammonium oxalate solution at 60° C.; the drying temperature in step (1) is 120° C., and the drying time is 12 h.

[0007] Preferably, in step (2), the particle size D50 of the ferromanganese oxalate is 5-8 μm; the particle size D50 of the first grinding is 300-450 nm; and the particle size D50 of the second grinding is 100-150 nm.

[0008] Preferably, the sodium source compound in step (2) is one or more of sodium dihydrogen phosphate, sodium oxalate, sodium chloride, sodium carbonate, sodium acetate, sodium pyrophosphate and sodium hydroxide.

[0009] Preferably, the phosphorus source compound in step (2) is one or more of phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, triammonium phosphate and diammonium hydrogen phosphate.

[0010] Preferably, the carbon source in step (2) is one or more of sodium citrate, citric acid, polyvinyl pyrrolidone, polyethylene glycol, glucose, ascorbic acid and sucrose.

[0011] Preferably, in the step (3), the particle size D50 of the precursor crushed is 5-10 μm and Dmax ≤ 30 μm.

[0012] Preferably, the organic solution in step (3) comprises ethanol, ether or acetone.

[0013] Preferably, the sintering temperature in step (3) is 550°C to 650°C; and the sintering is followed by heat preservation for a period of 8 to 12 hours.

[0014] The present invention also provides a sodium ion battery, which comprises a sodium iron manganese phosphate pyrophosphate positive electrode material prepared by the method described in the above technical solution.

[0015] The beneficial effects of the present invention are: (1) The sodium manganese iron phosphate pyrophosphate positive electrode material provided by the present invention has a stable crystal morphology, a high charge and discharge capacity and excellent rate performance.

[0016] (2) The primary in-situ carbon coating and secondary organic solvent vapor deposition coating provided by the present invention form a stable carbon coating on the surface of the positive electrode material, and the carbon coating is uniform; to a certain extent, it solves the problem of easy detachment of the carbon layer during the material processing.

[0017] (3) The present invention prepares phosphate pyrophosphate manganese iron positive electrode material by a solid phase method, which has a simple process, low cost and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0019] Figure 1 This is a SEM image of manganese ferrophosphate prepared in Example 1 of the present invention; Figure 2 The charge and discharge curves of Example 1 and Comparative Example 1 of the present invention are shown in FIG. DETAILED DESCRIPTION

[0020] The present invention provides a method for preparing a sodium ferromanganese phosphate pyrophosphate positive electrode material, wherein the chemical formula of the sodium ferromanganese phosphate pyrophosphate positive electrode material is: Na y Mn x Fe b [(PO4)2P2O7] t C1C2, wherein 4.05≤y≤4.1, 0.9≤x≤2.1, 0.9≤b≤2.1, 1.005≤t≤1.013; C1 is a primary in-situ carbon coating, and C2 is a secondary vapor deposition coating; the method comprises the following steps: (1) Mixing ferrous sulfate heptahydrate, manganese sulfate monohydrate and pure water to obtain a ferromanganese solution, wherein the molar ratio of iron ion concentration to manganese ion concentration in the ferromanganese solution is Mn:Fe=3-a:a, where a is 0.9≤a≤2.1; then adjusting the pH value to 2 with sulfuric acid; heating the ferromanganese solution under a nitrogen environment, wherein the heating condition is 400rpm and 60°C; then adding a 1 mol / L oxalic acid solution at 60°C to react, and adjusting the pH value to 2 with 6 mol / L ammonia water; then reacting for 3 hours, filtering, washing with an ammonium oxalate solution, and drying to obtain ferromanganese oxalate; (2) crushing ferromanganese oxalate, performing a first grinding, adding a sodium source compound, a phosphorus source compound and a carbon source, mixing evenly, performing a second grinding and spray drying to obtain a precursor; (3) The precursor is crushed and placed in a pot, and an organic solution is introduced into the pot under the protection of an inert gas for sintering to obtain a sodium manganese iron phosphate positive electrode material.

[0021] The present invention firstly mixes ferrous sulfate heptahydrate, manganese sulfate monohydrate and pure water to obtain a ferromanganese solution, and then adjusts the pH value to about 2 with sulfuric acid; the molar ratio of the iron ion concentration to the manganese ion concentration in the ferromanganese solution is Mn:Fe=3-a:a, and the value of a is preferably 0.9≤a≤2.1, and more preferably Mn:Fe=3:7 or Mn:Fe=5:5.

[0022] After adjusting the pH value with sulfuric acid, the present invention heats the ferromanganese solution under a nitrogen environment, and the heating conditions are 400rpm and 60°C; then, a 1 mol / L oxalic acid solution at 60°C is added for reaction, and the pH value is adjusted to about 2 with 6 mol / L ammonia water; after reacting for 3 hours, the solution is filtered, washed with an ammonium oxalate solution, and dried to obtain ferromanganese oxalate.

[0023] When adding the oxalic acid solution in the present invention, it is preferably added within 40 minutes, and the volume ratio of the oxalic acid solution to the ferromanganese solution is preferably 1:1; in the present invention, the ammonium oxalate solution is preferably a 0.1 mol / L ammonium oxalate solution at 60°C, and the volume ratio of the ammonium oxalate solution to the ferromanganese solution is preferably 26:10; the drying temperature is preferably 120°C, and the drying time is preferably 12 hours.

[0024] The method comprises crushing ferromanganese oxalate, performing a first grinding, adding a sodium source compound, a phosphorus source compound and a carbon source, mixing them evenly, performing a second grinding and spray drying to obtain a precursor.

[0025] In the present invention, the crushed particle size D50 of the manganese iron oxalate is preferably 5~8μm; the first grinding particle size D50 is preferably 300~450nm; the second grinding particle size D50 is preferably 100~150nm; the sodium source compound is preferably one or more of sodium dihydrogen phosphate, sodium oxalate, sodium chloride, sodium carbonate, sodium acetate, sodium pyrophosphate and sodium hydroxide; the phosphorus source compound is preferably one or more of phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, triammonium phosphate and diammonium hydrogen phosphate; the carbon source is preferably one or more of sodium citrate, citric acid, polyvinyl pyrrolidone, polyethylene glycol, glucose, ascorbic acid and sucrose.

[0026] After obtaining the precursor, the present invention crushes the precursor and then puts it into a pot, and introduces an organic solution under the protection of an inert gas for sintering to obtain the sodium iron manganese phosphate pyrophosphate positive electrode material.

[0027] In the present invention, the particle size D50 of the crushed precursor is preferably 5-10 μm, and Dmax ≤ 30 μm; the organic solution preferably includes ethanol, ether or acetone; the sintering temperature is preferably 550°C-650°C; the sintering time is preferably 2-6 hours, and more preferably 4 hours; the present invention also performs heat preservation after sintering, and the heat preservation time is preferably 8-12 hours, and more preferably 12 hours. The heat preservation stage in the present invention is conducive to making the crystal structure of sodium manganese iron pyrophosphate more stable, reducing the formation of impurity phases, and effectively improving its electrochemical performance and thermal stability, providing an important material basis for the practical application of sodium ion batteries.

[0028] The present invention also provides a sodium ion battery, which comprises a sodium iron manganese phosphate pyrophosphate positive electrode material prepared by the method described in the above technical solution.

[0029] In order to further illustrate the present invention, a method for preparing a sodium ferromanganese phosphate pyrophosphate positive electrode material provided by the present invention is described in detail below in conjunction with the accompanying drawings and examples, but they should not be understood as limiting the scope of protection of the present invention.

[0030] Unless otherwise specified, the raw materials and reagents involved in the embodiments of the present invention are conventional commercially available products.

[0031] Example 1 A sodium ferromanganese phosphate pyrophosphate positive electrode material, the preparation method of which comprises the following steps: (1) Take ferrous sulfate heptahydrate, manganese sulfate monohydrate and pure water to prepare 10L of ferromanganese solution, wherein the molar ratio of iron ion concentration to manganese ion concentration is Mn:Fe=3:7, and then adjust the pH value to about 2 with sulfuric acid to obtain 10L of ferromanganese solution; use oxalic acid to prepare oxalic acid solution with a concentration of 1 mol / L at 60°C, and keep it warm at 60°C; then add 10L of ferromanganese solution to a reactor, maintain the stirring speed of 400rpm, heat to 60°C and keep it warm, and pass nitrogen during the heating process; add the prepared oxalic acid solution to the reactor, control the speed to add it within about 40min, and adjust the pH value in the reactor to about 2 with 6mol / L ammonia water; after reacting for 3h, filter the reaction liquid, and wash it with 26L of ammonium oxalate solution with a temperature of 60°C and a concentration of 0.1mol / L, and after washing, dry the material at 120°C for 12h to obtain ferromanganese oxalate Fe 2.1 Mn 0.9 C2O4; (2) The ferromanganese oxalate obtained in step (1) is subjected to air flow pulverization, and the particle size D50 after pulverization is between 5.0 and 8 μm, and pure water is added and stirred evenly, so that the solid content of the final ferromanganese oxalate suspension is 30%; the ferromanganese oxalate suspension is ground using a sand mill, and the D50 after grinding is controlled to be 300 to 450 nm; then, according to the molar ratio of Fe 2.1 Mn 0.9 C2O4: Na2CO3: NH4H2PO4 = 3: 2.05: 4.05 sodium carbonate and diammonium phosphate were added, followed by 6% polyethylene glycol and 1.5% glucose accounting for the total solid weight; the grinding particle size D50 was controlled at 100-150nm; the precursor was obtained by spray drying; (3) The precursor obtained in step (2) is crushed by air flow, and the particle size D50 after crushing is 5-10 μm and Dmax ≤ 30 μm; under the protection of nitrogen, the temperature is raised to 600° C., ether solution is introduced for 4 hours, and the temperature is kept for 12 hours to obtain sodium manganese iron phosphate pyrophosphate positive electrode material.

[0032] Example 2 The same as Example 1, except that the time of introducing ether in step (4) is 2 h.

[0033] Example 3 The same as Example 1, except that the time of introducing ether in step (4) is 6 hours.

[0034] Example 4 The same as Example 1, the only difference is that in step (1), the molar ratio of iron ion concentration to manganese ion concentration in the ferromanganese solution is Mn:Fe=5:5.

[0035] Comparative Example 1 The same as Example 1, except that: in step (2), 3% of the total solid weight of glucose is added; and in the synthesis step (3), no ether is introduced.

[0036] Comparative Example 2 The same as Example 4, except that: in the synthesis step (2), 3% of the total solid weight of glucose is added; and in the synthesis step (3), no ether is introduced.

[0037] Test Example 1 The samples prepared in the examples and comparative examples were tested for carbon content and button cell, and the results are shown in Table 1.

[0038] The testing method of button cells is as follows: assemble a slurry with a mass ratio of sample: Superp: PVDF of 90:5:5 into a button cell and test it under a cut-off voltage of 2.0~4.2V.

[0039] Table 1 Material test results of Examples 1 to 4 and Comparative Examples 1 to 2 In Examples 1 to 3, the content of secondary carbon coating is controlled by changing the time of passing the ether solution. As time goes by, the carbon content gradually increases. When the time of passing the ether solution is 4 hours and the carbon content is 1.69%, the sodium ferromanganese phosphate pyrophosphate positive electrode material has the best electrochemical performance. The results of Examples 1 to 4 and Comparative Examples 1 to 2 show that whether the molar ratio of Mn:Fe is 5:5 or 6:4, the charge / discharge capacity of the prepared positive electrode material is better than that of the control sample without passing the ether solution when the ether solution is passed during the sintering process.

[0040] For the sodium manganese iron phosphate positive electrode material, the introduction of Mn will reduce the structural stability and cyclability of the mixed phosphate. 3+ The Jahn-Teller effect will cause the structure to collapse during the charge and discharge process, and the capacity and cycle performance will decay rapidly. Carbon coating is an effective way to solve the above problems; however, the first in-situ carbon coating has uneven and incomplete coating, and the carbon layer falls off during the crushing stage; while the present invention uses high-temperature vaporization and carbonization of ether, followed by a second high-temperature coating on the material surface, repairing the surface that was not coated by the first in-situ carbon coating and the uneven coating; and it is not easy to fall off during the subsequent processing, achieving relatively ideal electrochemical performance.

[0041] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing sodium ferromanganese phosphate pyrophosphate positive electrode material, characterized in that: The chemical formula of the sodium iron manganese phosphate pyrophosphate positive electrode material is: Na y Mn x Fe b [(PO4)2P2O7] t C1C2, wherein 4.05≤y≤4.1, 0.9≤x≤2.1, 0.9≤b≤2.1, 1.005≤t≤1.013; C1 is a primary in-situ carbon coating, and C2 is a secondary vapor deposition coating; the method comprises the following steps: (1) Mixing ferrous sulfate heptahydrate, manganese sulfate monohydrate and pure water to obtain a ferromanganese solution, wherein the molar ratio of iron ion concentration to manganese ion concentration in the ferromanganese solution is Mn:Fe=3-a:a, where a is 0.9≤a≤2.1; then adjusting the pH value to 2 with sulfuric acid; heating the ferromanganese solution under a nitrogen environment, wherein the heating condition is 400rpm and 60°C; then adding a 1 mol / L oxalic acid solution at 60°C to react, and adjusting the pH value to 2 with 6 mol / L ammonia water; then reacting for 3 hours, filtering, washing with an ammonium oxalate solution, and drying to obtain ferromanganese oxalate; (2) crushing ferromanganese oxalate, performing a first grinding, adding a sodium source compound, a phosphorus source compound and a carbon source, mixing evenly, performing a second grinding and spray drying to obtain a precursor; (3) The precursor is crushed and placed in a pot, and an organic solution is introduced into the pot under the protection of an inert gas for sintering to obtain a sodium manganese iron phosphate positive electrode material.

2. The preparation method according to claim 1, characterized in that: The ammonium oxalate solution is a 0.1 mol / L ammonium oxalate solution at 60° C.; the drying temperature in step (1) is 120° C., and the drying time is 12 hours.

3. The preparation method according to claim 1, characterized in that: In the step (2), the particle size D50 of the ferromanganese oxalate is 5-8 μm; the particle size D50 of the first grinding is 300-450 nm; and the particle size D50 of the second grinding is 100-150 nm.

4. The preparation method according to claim 1, characterized in that: The sodium source compound in step (2) is one or more of sodium dihydrogen phosphate, sodium oxalate, sodium chloride, sodium carbonate, sodium acetate, sodium pyrophosphate and sodium hydroxide.

5. The preparation method according to claim 1, characterized in that: The phosphorus source compound in step (2) is one or more of phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, triammonium phosphate and diammonium hydrogen phosphate.

6. The preparation method according to claim 1, characterized in that: In the step (2), the carbon source is one or more of sodium citrate, citric acid, polyvinyl pyrrolidone, polyethylene glycol, glucose, ascorbic acid and sucrose.

7. The preparation method according to claim 1, characterized in that: In the step (3), the particle size D50 of the precursor crushed is 5-10 μm and Dmax ≤ 30 μm.

8. The preparation method according to claim 1, characterized in that: The organic solution in step (3) includes ethanol, ether or acetone.

9. The preparation method according to claim 1, characterized in that: The sintering temperature in step (3) is 550°C to 650°C; after sintering, the sintering is further carried out, and the insulation time is 8 to 12 hours.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises a sodium iron manganese phosphate pyrophosphate positive electrode material prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Sodium ion battery polyanion positive electrode material / C composite material and preparation method thereof

    CN116825981A

  • Composite carbon source coated lithium manganese iron phosphate positive electrode material and preparation method and application thereof

    CN118684207A

  • High-entropy ferric sodium phosphate pyrophosphate precursor and high-entropy ferric sodium phosphate pyrophosphate positive electrode material

    CN118684208A

  • Preparation method of ferromanganese phosphate, ferromanganese phosphate, positive electrode material and battery

    CN118929612A

  • Sodium Battery Cathode Electrode Material and Preparation Method and Application Thereof

    US20240405206A1

Cited By

  • Modified ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof

    CN120834200A